Mesh for down filler, ultra-light down filler, and method for producing same

By adopting a specific combination of fiber structure design in down fillers, the problems of cold spot and poor elasticity of existing down fillers are solved, and high warmth and excellent drying performance are achieved.

CN119507119AActive Publication Date: 2025-02-25TP INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311285401.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-08
Filing Date
2023-10-07
Publication Date
2025-02-25
Estimated Expiration
2043-10-07

AI Technical Summary

Technical Problem

The existing down filler has cold spot problems that lead to reduced warmth performance and poor elasticity and resilience, which cannot meet the lightness and mobility requirements of the latest fashion trends.

Method used

A single-piece sheet-shaped down filler mesh with no pinholes, including mixed down, non-stretched low-melting point leather-core composite fibers, hollow conjugated stretched staple fibers and ordinary solid silicide fibers, through specific fibers Proportional and structural design enhances the elasticity and resilience of down fillers.

Benefits of technology

It realizes down filler without cold spots, has excellent warmth, heat insulation, elasticity and restoration, and has excellent drying performance, so there is no problem of down separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507119A_ABST
    Figure CN119507119A_ABST
Patent Text Reader

Abstract

The present invention relates to a mesh for a down filler, an ultra-light down filler, and a method for manufacturing the same, and more specifically, to an ultra-light down filler having a thin thickness, excellent warmth retention, and excellent four-direction (or multi-direction) elasticity, and a mesh for a down filler for manufacturing the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ultralight down filler which is thin in thickness but excellent in warmth retention and four-way (or multi-way) elasticity, a down filler mesh used for manufacturing the same and a manufacturing method thereof. Background Art

[0002] Down products made of duck or goose down have excellent warmth retention properties due to the large amount of air contained between the down hairs. As cold-proof clothing used to maintain body temperature during outdoor activities in winter, down products have become a popular high-end product in the market.

[0003] As these down products become a winter fashion staple, popularity of ultralight down jackets that are easy to carry and carry continues to rise, so a lot of development is being done in terms of warmth and lightness.

[0004] However, if down filling is made of down, it lacks restoring power and supporting power, and the down shedding from the seams and the peculiar smell of down have become factors of dissatisfaction for consumers. In addition, some people have pointed out the poor appearance and difficulty in washing of products caused by the clumping of down. In order to prevent down products from shedding or knotting, the core layer of the down filling (a mesh composed of down) and the lining are sewn together and cut into a structure with multiple compartment structures, or the lining is sewn together with the outer fabric and the down is filled into the compartments after being cut into a structure with multiple compartment structures to manufacture the down filling. The down filling is manufactured in a state where the down is filled inside the multiple compartment structures, that is, in a state where the down is filled between the seams (for example, a quilted structure, etc.). However, the down filling of this structure has the problem of reducing the warmth retention performance due to the generation of cold spots.

[0005] In addition, the trend of clothing products in recent years has emphasized not only design but also activity, and the down filling of the above-mentioned compartment structure has poor elasticity and recovery, and because the thickness of the down filling is made too thick to ensure high thermal insulation and warmth, there is also a problem of not conforming to the latest fashion trends.

[0006] Prior art literature

[0007] Patent Literature

[0008] Korean Patent No. 10-1334624 (Announcement Date: November 25, 2013)

[0009] Korean Patent No. 10-1669938 (Announcement Date: October 21, 2016) Summary of the invention

[0010] Technical issues

[0011] The present invention aims to provide a mesh for down filling and an ultralight down filling using the same as a filling (or a mesh layer), wherein the mesh for down filling not only does not include a compartment structure that causes cold spots in the down filling, but is also manufactured as a pinhole-free, one-piece sheet, and its components are optimized, so that the elasticity and recovery of the down filling can be greatly increased while having excellent warmth retention.

[0012] Means of solving the problem

[0013] In order to solve the above problems, the mesh material for down filling of the present invention includes: a mixed down including one or more selected from goose down and duck down; a non-stretchable low melting point (Low Melting) core-sheath composite fiber; a hollow conjugate stretch (HCT) short fiber and a regular solid siliconized fiber (RSS) short fiber.

[0014] As a preferred embodiment of the present invention, the mixed down comprises 15 to 30 weight % of feathers and 70 to 85 weight % of down.

[0015] As a preferred embodiment of the present invention, the melting point of the sheath of the non-stretchable low-melting-point sheath-core composite fiber is 100° C. to 150° C., and the melting point of the core is above 250° C.

[0016] According to a preferred embodiment of the present invention, the non-stretchable low-melting-point core-sheath composite fiber has an average fineness of 3.0 de to 5.0 de, and an average fiber length of 45 mm to 60 mm.

[0017] According to a preferred embodiment of the present invention, the melting points of the HCT short fibers and the RSS short fibers are both above 260°C.

[0018] According to a preferred embodiment of the present invention, the average fineness of the HCT staple fibers is 2.0 de to 3.5 de, the average fiber length is 45 mm to 60 mm, and the number of crimps is 15 to 23 per inch.

[0019] According to a preferred embodiment of the present invention, the average fineness of the RSS staple fibers is 2.0 de to 3.5 de, and the average fiber length is 45 mm to 60 mm.

[0020] According to a preferred embodiment of the present invention, the down filling web of the present invention comprises 25.0 wt % to 50.0 wt % of the mixed down, 9.0 wt % to 18.0 wt % of the HCT short fibers, 13.0 wt % to 21.0 wt % of the RSS short fibers and the balance of 100 wt % of the non-stretchable low-melting core-sheath composite fibers.

[0021] According to a preferred embodiment of the present invention, the basis weight of the down filling mesh of the present invention can be 70g / m 2 Up to 150g / m 2 .

[0022] Another object of the present invention is to provide an ultra-light down filling with high four-way elasticity and high warmth retention, the down filling comprising: a mesh layer composed of the mesh for down filling described above; and a sheet layer stacked on the upper and lower parts of the mesh layer and combined with the mesh layer.

[0023] As a preferred embodiment of the present invention, the down filling of the present invention is a composite sheet material which is a combination of a mesh layer and a thin sheet layer and does not include a cell structure and pinholes which generate cold spots.

[0024] As a preferred embodiment of the present invention, the sheet layer may include a multi-directional stretch fabric woven from high-elastic polyester yarn and having a net structure.

[0025] As a preferred embodiment of the present invention, an acrylic resin layer may be included between the mesh layer and the sheet layer.

[0026] As a preferred embodiment of the present invention, when the basis weight of the web layer of the present invention is 80 g / m 2 Up to 100g / m 2 When measured according to ASTM D1518, the thermal insulation capacity can meet 2.00CLO or above.

[0027] As a preferred embodiment of the present invention, when the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 When the air permeability of the down filling of the present invention is measured according to the ASTM D737 method, it can meet 100 cubic feet per minute (CFM, Cubiefeet per minute) or more.

[0028] As a preferred embodiment of the present invention, when the basis weight of the down filling of the present invention is 80 g / m 2 Up to 100g / m 2 When the drying rate after 1 hour measured according to the JIS L 1096 method can satisfy 30.0% or more.

[0029] According to a preferred embodiment of the present invention, when the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 When the down filling material is used as the filling material, the recovery rate of the down filling material of the present invention can meet 83.0% or more.

[0030] As a preferred embodiment of the present invention, when the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 The residual extension (Residual Extension) after 30 seconds measured by ASTM D3107 method and calculated by Formula 2 can satisfy 6.5% or less in the longitudinal direction and 8.0% or less in the transverse direction.

[0031] As a preferred embodiment of the present invention, when the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 The residual extension (Residual Extension) after 30 minutes measured by ASTM D3107 method and calculated by Formula 2 can meet the requirements of 3.0% or less in the longitudinal direction and 4.5% or less in the transverse direction.

[0032] [Formula 2]

[0033] Residual Extension = growth, %) = [{(original length + unrecovered length) - original length} / original length] X 100%

[0034] As a preferred embodiment of the present invention, when the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 The recovery rate (Recovery) of the down filling of the present invention after 30 seconds measured according to the ASTM D3107 method and calculated by Formula 3 can meet 70.0% or more in the longitudinal direction and 65.0% or more in the transverse direction.

[0035] As a preferred embodiment of the present invention, when the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 The recovery rate (Recovery) of the down filling of the present invention after 30 minutes measured according to the ASTM D3107 method and calculated by Formula 3 can meet 75.0% or more in the longitudinal direction and 75.0% or more in the transverse direction.

[0036] [Formula 3]

[0037] Recovery rate (%) = [{maximum extension length - (original length + unrecovered length)} / (maximum extension length - original length)] X 100%

[0038] Another object of the present invention relates to a method for manufacturing the ultra-light down filling with high elasticity and high warmth retention in four directions, which can be manufactured by performing the following processes: step 1, supplying yarn in a bale state to a supply unit; step 2, performing bale breaking and opening processes on the yarn supplied to the supply unit respectively; step 3, carding the opened yarn; step 4, processing the carded yarn into a web; step 5, coating acrylic resin on both sides of the web, and then performing a drying process; and step 6, performing surface heat treatment on the web fixed with acrylic resin, laminating thin sheets on both sides of the web, then rolling with a heating roll, and then packaging.

[0039] Effects of the Invention

[0040] The down filling of the present invention is an ultra-light down filling, which has no cold spots and has excellent warmth retention, heat insulation, elasticity and resilience. In addition, compared with existing down fillings, the down filling of the present invention has excellent drying performance and does not have down separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a schematic diagram of the cross-sectional structure of the down filler of the present invention.

[0042] Figure 2 It is a schematic diagram of the manufacturing process of the down filling of the present invention.

[0043] Figure 3 Part A and Part B are photographs of the down filling produced in Example 1.

[0044] Figure 4 This is a photograph of the device used for elasticity measurement in Experimental Example 2.

[0045] Description of Reference Numerals

[0046] 1: mesh material (layer) for down filling; 100, 100': sheet layer; 10: feather; 20: down; 30: RSS short fiber; 40: HCT short fiber DETAILED DESCRIPTION

[0047] The term "non-stretchability" used in this specification means having very low elongation and recovery, and refers to the property that the fiber cannot return to its original shape after being stretched by an external force due to low elasticity.

[0048] The term "four-way" used in this specification refers to two directions in a certain direction in which the down filling is stretched in a two-dimensional plane and two directions perpendicular thereto.

[0049] Hereinafter, the present invention will be described in more detail.

[0050] The down filling net of the present invention is a net without cold spots and a sheet-like net without a cell structure and pinholes.

[0051] The down filling mesh of the present invention may include: mixed down including one or more selected from goose down and duck down; non-stretchable low melting point (Low Melting) core-skin composite fiber; hollow conjugate stretch (HCT) short fiber and regular solid siliconized fiber (RSS) short fiber.

[0052] The mixed down includes at least one selected from goose down and duck down. At this time, the mixed down refers to the mixing of feathers and down, rather than the mixing of goose down and / or duck down.

[0053] In addition, the mixed down may include 15 to 30% by weight of feathers and 70 to 85% by weight of down, preferably, 15 to 25% by weight of feathers and the remainder of 100% by weight of down, more preferably, 17.5 to 22.5% by weight of feathers and the remainder of 100% by weight of down. At this time, if the feather content is less than 15.0% by weight, there may be a problem that the price competitiveness is greatly reduced due to the excessively high down content; if the feather content exceeds 30.0% by weight, the warmth retention may be slightly reduced, and there may be a problem that the product surface is uneven, so considering the warmth retention and commercial properties, it is preferred to use feathers and down within the above range.

[0054] The non-stretchable low-melting core-sheath composite fiber is a fiber that plays a role in binding the mixed down and other fibers in the web together and in stabilizing the shape of the web, and is a fiber that has no stretchability (elasticity).

[0055] The sheath of the non-stretchable low-melting core-sheath composite fiber may be composed of polyethylene terephthalate (PET) resin, and the melting point of the PET resin is 100° C. to 150° C., preferably 105° C. to 130° C., and more preferably 105° C. to 120° C. In addition, the core of the non-stretchable low-melting core-sheath composite fiber may be composed of PET resin, and the melting point of the PET resin is 250° C. or more, preferably 250° C. to 280° C., and more preferably 255° C. to 275° C.

[0056] At this time, if the melting point of the resin forming the sheath is lower than 100°C, there may be a problem of poor fusion, and if the melting point of the resin forming the sheath exceeds 150°C, there may be a problem of hardening of the product. In addition, if the melting point of the resin forming the core is lower than 250°C, there may be a problem of loose connection between the yarns, and if the melting point of the resin forming the core exceeds 280°C, there may be a problem of hardening and curing of the connection between the yarns.

[0057] In addition, the composite fiber of the non-stretchable low-melting point core-sheath composite fiber can use an average fineness of 3.0de to 5.0de and an average fiber length of 45㎜ to 60㎜. Preferably, the average fineness of 3.5de to 4.7de and the average fiber length of 45㎜ to 58㎜ can be used. More preferably, the average fineness of 3.7de to 4.5de and the average fiber length of 48㎜ to 55㎜ can be used. At this time, if the average fineness of the non-stretchable low-melting point core-sheath composite fiber is less than 3.0de, there may be a problem of reduced thickness, and if the average fineness of the non-stretchable low-melting point core-sheath composite fiber exceeds 5.0de, there may be a problem of poor touch of the product. In addition, if the average fiber length of the non-stretchable low-melting point core-sheath composite fiber is less than 45㎜, there may be a problem of poor bonding between yarns, and if the average fiber length exceeds 60.0㎜, there may be a problem of yarn entanglement and thickness reduction.

[0058] Secondly, the RSS staple fibers constituting the mesh are fibers that play a role in improving the strength, flexibility and softness of the mesh, and are fibers that are non-thermofusible under the mesh manufacturing process and the down filling process conditions using the same. Therefore, the RSS staple fibers are fibers that satisfy a melting point of 260°C or above, preferably fibers that satisfy a melting point of 260°C to 300°C. As a preferred example, the RSS staple fibers can use polyester fibers coated with silicone to increase miscibility with other fibers. Preferably, for example, PET fibers mixed with fatty alcohols, mixed phosphate mixtures, low molecular weight alcohol mixtures and silicone emulsions on 100% polyethylene terephthalate (PET) regular staple fibers can be used as RSS staple fibers.

[0059] In addition, the RSS staple fibers may have an average fineness of 2.0 to 3.5 de, an average fiber length of 45 to 60 mm, and a crimp number of 15 to 23 per inch. Preferably, the fibers may have an average fineness of 2.0 to 3.0 de, an average fiber length of 45 to 58 mm, and a crimp number of 17 to 23 per inch. More preferably, the fibers may have an average fineness of 2.2 to 2.8 de, an average fiber length of 48 to 55 mm, and a crimp number of 18 to 22 per inch. At this time, if the average fineness of the RSS staple fibers is less than 2.0 de, there may be a problem of poor bonding due to insufficient yarn strength, and if the average fineness of the RSS staple fibers exceeds 3.0 de, there may be a problem of reduced soft touch of the product. In addition, if the average fiber length of the RSS staple fiber is less than 45 mm, there may be a problem of poor bonding between the yarns, and if the average fiber length exceeds 60.0 mm, there may be a problem of yarn entanglement and thickness reduction. In addition, if the number of crimps of the RSS staple fiber is less than 15 / inch, there may be a problem of reduced restoring force, and if the number of crimps exceeds 23 / inch, there may be a problem of reduced bonding between the yarns.

[0060] Secondly, the HCT short fibers constituting the mesh are fibers that play a role in providing elasticity and restoring force to the mesh, and the HCT short fibers are fibers having a melting point of 260° C. or higher, preferably 265° C. or higher. As a preferred example, the HCT short fibers may be polyester fibers that meet the above melting point, and more preferably polyethylene terephthalate (PET) fibers.

[0061] In addition, the HCT staple fiber can be a fiber with an average fineness of 2.0de to 3.5de and an average fiber length of 45㎜ to 60㎜, preferably, a fiber with an average fineness of 2.0de to 3.0de and an average fiber length of 45㎜ to 58㎜ can be used, and more preferably, a fiber with an average fineness of 2.2de to 2.8de and an average fiber length of 48㎜ to 55㎜ can be used. At this time, if the average fineness of the HCT staple fiber is less than 2.0de, there may be a problem of reduced elasticity, and if the average fineness of the HCT staple fiber exceeds 3.0de, there may be a problem of reduced elasticity. In addition, if the average fiber length of the HCT staple fiber is less than 45㎜, there may be a problem of reduced bonding force, and if the average fiber length exceeds 60.0㎜, there may be a problem of yarn entanglement and thickness reduction.

[0062] The down filling web of the present invention composed of the above-mentioned fibers may include 25.0 to 50.0% by weight of the mixed down, 9.0 to 18.0% by weight of the HCT short fibers, 13.0 to 21.0% by weight of the RSS short fibers, and the balance of 100% by weight of the non-stretchable low-melting core-sheath composite fibers; preferably, it may include 28 to 45% by weight of the mixed down, 9.5 to 16.5% by weight of the HCT short fibers, 14.0 to 21.0% by weight of the RSS short fibers, and the balance of 100% by weight of the non-stretchable low-melting core-sheath composite fibers; more preferably, it may include 29 to 42% by weight of the mixed down, 9.8 to 16.3% by weight of the HCT short fibers, 14.0 to 20.5% by weight of the RSS short fibers, and the balance of 100% by weight of the non-stretchable low-melting core-sheath composite fibers. At this time, if the content of mixed down in the mesh is less than 25% by weight, the warmth retention may be insufficient, and if it exceeds 50% by weight, the content of other fibers will be relatively reduced, so it may not be suitable for down fillings with high elasticity and resilience manufactured by using the mesh. In addition, if the content of HCT short fibers in the mesh is less than 9% by weight, there may be a problem of reduced elasticity and elasticity of the mesh, and if it exceeds 18% by weight, since higher elasticity cannot be expected, it is preferred to use HCT short fibers within the above range. In addition, if the content of RSS short fibers in the mesh is less than 13% by weight, commercial properties and processing performance may decrease due to insufficient strength and flexibility of the mesh, and if its usage exceeds 22% by weight, although it is beneficial to increase the strength of the mesh, the warmth retention may be relatively reduced, so it is preferred to use it within the above range.

[0063] In order to ensure the thinness, ultralightness and high warmth retention of the down filling material applied to the mesh, the basis weight of the down filling mesh (single-layer mesh and / or composite mesh) of the present invention is 70 g / m 2 Up to 150g / m 2 , preferably 75g / m 2 Up to 140g / m 2 , more preferably 78g / m 2 Up to 135g / m 2 .

[0064] The following describes the ultralight down filling with high elasticity and high warmth retention in four directions of the present invention. Figure 1As shown in the schematic diagram of , it includes: a mesh layer 1, which is composed of the mesh for down filling as described above; and thin sheet layers 100 and 100', which are stacked on the upper and lower parts of the mesh layer and combined with the mesh layer, and the mesh layer and the thin sheet layer are a composite sheet that is combined into one without cold spots.

[0065] Additionally, an acrylic resin layer may be included between the mesh layer and the sheet layer.

[0066] In addition, the sheet layer may be a multi-directional stretch fabric woven from high-elastic polyester yarn and having a net structure.

[0067] The down filling of the present invention can be Figure 2 More specifically, the following steps can be performed to manufacture the yarn: step 1, supplying the yarn in a bale state to a supply unit; step 2, performing bale breaking and opening processes on the yarn supplied to the supply unit; step 3, carding the opened yarn; step 4, processing the carded yarn into a web; step 5, coating both sides of the web with acrylic resin, and then performing a drying process; and step 6, performing surface heat treatment on the web fixed with acrylic resin, laminating thin sheets on both sides of the web, then rolling with a heating roll, and then packaging.

[0068] When the basis weight of the mesh layer of the down filling of the present invention is 80 g / m 2 Up to 100g / m 2 When the thermal insulation capacity is measured according to the ASTM D1518 method, it can meet 2.00CLO or more, preferably meet 2.05CLO to 3.00CLO, and more preferably meet 2.10CLO to 2.96CLO.

[0069] In addition, when the basis weight of the mesh layer of the down filling of the present invention is 80 g / m 2 Up to 100g / m 2 When the air permeability is measured according to the ASTM D737 method, it can meet 100.0 cubic feet per minute (CFM) or more, preferably 120.0 CFM to 150.000 CFM, and more preferably 125.0 CFM to 145.000 CFM.

[0070] In addition, when the basis weight of the mesh layer of the down filling of the present invention is 80 g / m 2 Up to 100g / m 2When the drying rate after 1 hour measured according to JIS L1096 method can satisfy 30.0% or more, the drying rate after 1 hour preferably satisfies 31.0% to 40.0%, and more preferably satisfies 31.0% to 38.5%.

[0071] In addition, when the basis weight of the mesh layer of the down filling of the present invention is 80 g / m 2 Up to 100g / m 2 When the recovery rate is 83.0% or more, the recovery rate is preferably 85.0% to 92.0%, and more preferably 85.0% to 90.0%.

[0072] In addition, when the basis weight of the mesh layer of the down filling of the present invention is 80 g / m 2 Up to 100g / m 2 The residual extension after 30 seconds measured according to the ASTM D3107 method and calculated by the following formula 2 can satisfy 6.5% or less in the longitudinal direction and 8.0% or less in the transverse direction, preferably 1.0% to 6.2% in the longitudinal direction and 3.0% to 7.0% in the transverse direction, and more preferably 1.4% to 6.0% in the longitudinal direction and 3.5% to 6.7% in the transverse direction.

[0073] In addition, when the residual elongation after 30 minutes is measured by the same method, it satisfies less than 5.0% in the longitudinal direction and less than 4.5% in the transverse direction, preferably satisfies 1.0% to 4.8% in the longitudinal direction and 1.2% to 4.5% in the transverse direction, and more preferably can satisfy 1.0% to 4.5% in the longitudinal direction and 2.0% to 4.2% in the transverse direction.

[0074] Here, the longitudinal direction refers to the warp direction of the fabric constituting the sheet layer of the down filling, and the transverse direction refers to the weft direction of the fabric constituting the sheet layer of the down filling.

[0075] [Formula 2]

[0076] Residual Extension = growth, %) = [{(original length + unrecovered length) - original length} / original length] X 100%

[0077] In addition, when the basis weight of the mesh layer of the down filling of the present invention is 80 g / m 2 Up to 100g / m 2The recovery rate (Recovery) after 30 seconds measured according to the ASTM D3107 method and calculated by Formula 3 can satisfy more than 70.0% in the longitudinal direction and more than 65.0% in the transverse direction, preferably satisfying 70.0% to 86.0% in the longitudinal direction and 65.0% to 80.0% in the transverse direction, and more preferably satisfying 65.0% to 85.0% in the longitudinal direction and 66.5% to 80.0% in the transverse direction.

[0078] In addition, when the recovery rate after 30 minutes is measured by the same method, it satisfies more than 75.0% in the longitudinal direction and more than 75.0% in the transverse direction, preferably satisfies 76.0% to 90.0% in the longitudinal direction and 76.5% to 87.5% in the transverse direction, and more preferably can satisfy 77.5% to 89.0% in the longitudinal direction and 77.0% to 87.0% in the transverse direction.

[0079] Here, the longitudinal direction refers to the warp direction of the fabric constituting the sheet layer of the down filling, and the transverse direction refers to the weft direction of the fabric constituting the sheet layer of the down filling.

[0080] [Formula 3]

[0081] Recovery rate (%) = [{maximum extension length - (original length + unrecovered length)} / (maximum extension length - original length)] X 100%

[0082] The present invention is described in more detail below by way of examples, but it should be understood that the following examples do not limit the scope of the present invention, but are intended to help understand the present invention.

[0083] [Example]

[0084] Example 1: Production of down filling

[0085] Mixed down containing 20% ​​by weight of duck feathers and 80% by weight of duck down was prepared in a packaged state.

[0086] A non-stretchable low-melting core-sheath composite fiber (manufacturer: Huvis, trade name: LMF) having an average fineness of 4 de and an average fiber length of 51 mm was prepared. At this time, the composite fiber was a fiber in which the sheath was composed of polyethylene terephthalate with a melting point of 110° C. and the core was composed of PET resin with a melting point of 250° C., and the cross-sectional area ratio of the core to the sheath was 1:1.

[0087] Silicon-coated polyethylene terephthalate (PET) fibers (manufacturer: Huvis, trade name: regular staple fibers) with a melting point of 260° C. or higher were prepared as regular solid siliconized fibers (RSS) having an average fineness of 2.5 de and an average fiber length of 51 mm.

[0088] PET fibers (manufacturer: Huvis, trade name: ZENTRA) with a melting point of 260° C. or higher were prepared as hollow conjugate stretch (HCT) short fibers. The HCT fibers had an average fineness of 2.5 de and a fiber length of 51 mm.

[0089] The mixed down, non-stretch low melting point core-sheath composite fiber, RSS short fiber and HCT short fiber are supplied as yarns and Figure 2 The process schematically shown in Figure 1 produces down filling.

[0090] The yarn is supplied to a supply unit, and bale breaking and opening processes are performed.

[0091] Next, the unpacked yarn is transferred using a carding machine and subjected to a carding process.

[0092] Next, the carded yarn is transferred to a web forming unit and processed into a web, thereby manufacturing a web.

[0093] Next, the mesh is transferred to a drying unit, where acrylic resin (manufacturer: WOLSUNG VINA, trade name: MEDIUM RESIN) is sprayed on one surface of the mesh, followed by primary drying, and acrylic resin is sprayed on the other surface of the mesh again, followed by secondary drying, thereby fixing the acrylic resin on the upper and lower parts of the mesh. At this time, the drying temperature is 145°C to 155°C, and the above two sprayings and primary and secondary drying are continuous processes.

[0094] Next, the mesh formed with the acrylic resin layer is transferred to a heat treatment unit and subjected to surface heat treatment at 310°C to 350°C, and then transferred to a sheet supply unit and a multi-directional stretch fabric having a net structure woven from high-elastic polyester yarn (manufacturer: Chargeurs PCC, product name: #6029) is laminated on both upper and lower surfaces of the mesh.

[0095] Next, integration is achieved by pressing using a heating roll, and then packaging to manufacture an integrated composite sheet-like down filling.

[0096] The manufactured down filling is composed of a single-layer mesh and an integrated sheet layer stacked and bonded on the upper and lower parts of the mesh. The photo of the manufactured down filling is shown in FIG. Figure 3 As shown in Part A and Part B.

[0097] In addition, the web is composed of 30% by weight of mixed down, 17% by weight of HCT short fibers, 17% by weight of RSS short fibers, and 36% by weight of non-stretchable low-melting-point core-skin composite fibers, with a basis weight of 100 g / m 2 .

[0098] Examples 2 to 6 and Comparative Examples 1 to 6

[0099] Down fillings were manufactured in the same manner as in Example 1, wherein the content or basis weight of the fibers inside the web was set differently according to Table 1 below, thereby manufacturing down fillings to implement Examples 2 to 6 and Comparative Examples 1 to 6, respectively.

[0100] However, in Examples 3 to 6 and Comparative Examples 1 to 6, as a multidirectional stretch fabric constituting a sheet layer on both the upper and lower surfaces of the mesh of the down filling, a stretch fabric (manufacturer: Picardy, product name: 6029) was used instead of the stretch fabric of Example 1 (manufacturer: Wonyoung, product name: J30G) and the stretch fabric of Example 2 (manufacturer: Sejin, product name: 3015F) and down filling was manufactured.

[0101]

Table 1

[0102]

[0103] Experimental Example 1: Measurement of warmth retention, quick drying, breathability, lint loss, and recovery

[0104] The tests for evaluating the heat insulation, quick-drying, air permeability and hair loss of the down fillings produced in the above-mentioned embodiments and comparative examples were commissioned to Intertek Testing Services Korea Ltd and ID FL Laboratory and Institute.

[0105] In addition, control group 1 is 50% by weight of mixed down containing 20% ​​by weight of duck feathers and 80% by weight of duck down, 35% by weight of sorona fiber and 15% by weight of PET fiber with a basis weight of 80 g / m 2 Down filling.

[0106] In addition, control group 2 was 85% by weight of mixed down containing 20% ​​by weight of duck feathers and 80% by weight of duck down and 15% by weight of polyester fiber with a basis weight of 80 g / m 2 Down filling.

[0107] In addition, control group 3 was made of 100% polyester with a basis weight of 80 g / m 2 Down filling (trade name: syncloud basic GRS).

[0108] (1) Measurement method of thermal insulation

[0109] The test method was measured according to ASTM D1518. The specific test method is as follows.

[0110] 1) Place a cover on the bare board (heat generating body, set to 35°C), and set the ambient temperature of the chamber to 20°C and the humidity to 65%.

[0111] 2) When the ambient temperature, humidity, and heat exchange between bare boards are stable, measure the thermal insulation of the bare boards (Rct0).

[0112] 3) Place the test piece on a bare board to prevent wrinkles or tension, and perform 1) and 2) in sequence. At this point, the test piece is in a mock-up or product (sheet type padding) state, with a size of 550 mm wide x 550 mm high.

[0113] 4) When the ambient temperature, humidity, and heat exchange between the bare board and the specimen are stable, measure the thermal insulation (Rct) of the specimen.

[0114] 5) The result value of warmth retention (CLO) = (Rct-Rct0)X6.45 was obtained.

[0115] The warmth retention of 1CLO is a unit representing thermal resistance, and the heat dissipation is 58W / m when the wind speed is 0.1m / s and the ambient temperature is 21℃. 2 A comfortable warm state. 1 clo is equal to 0.155K·m 2 / W.

[0116] The measurement results of the thermal insulation are shown in Table 2 below. The higher the value of the thermal insulation unit CLO, the better the thermal insulation.

[0117] (2) Measurement method of quick-drying properties

[0118] The test method was measured according to JIS L 1096:2010. The specific test method is as follows.

[0119] 1) Prepare a mock-up specimen with a length of 400 mm and a width of 400 mm.

[0120] 2) Fully immerse the specimen in distilled water at 20℃ (±2℃).

[0121] 3) Take it out of the water and install it on the device when water drops no longer fall.

[0122] 4) Place it in a test room under standard conditions and measure the time required for it to dry naturally and return to its original weight. The average value is expressed as an integer, and the drying rate (%) and complete drying time after 1 hour are measured.

[0123] (3) Measurement method of air permeability

[0124] The test method was measured according to ASTM D737. The specific test method is as follows.

[0125] 1) After adjustment, perform equipment calibration.

[0126] 2) After confirming that the "0" dl is measured with the reference material, the test piece is mounted on the test piece platform to ensure that there are no wrinkles or folds. At this time, the down filler itself is used as the test piece, with a size of 550㎜ wide × 550㎜ high.

[0127] 3) Record the measured results and take the average of 10 repeated tests as the measured value. In addition, the test area (Test area: 38cm 2 ) and test pressure (Test pressure: 125pa) for measurement.

[0128] (4) Measurement method of hair loss

[0129] The test method is measured according to FED STD FTMS 5530 International Method (based on Federal Standard 191-5530), and the number of hair loss is less than 5 to be qualified. The test conditions are the size of the tumbling box (Size of Tumbl ing Box) 45cm x 45cm x 45cm (width, length, height), the number of revolutions per minute (RPM, Revolution per Minute) 48 (± 2) and the duration of tumbling (Duration of Tumbling) 30 minutes.

[0130] (5) Measurement method of recovery

[0131] Recovery was measured in the following manner.

[0132] 1) Prepare the test piece for measuring the restoring force.

[0133] 2) After laying the specimen flat, measure the height (Hb) before starting in units of 1 mm.

[0134] 3) Place in a constant temperature and humidity chamber and place a 1 kg hammer on it for 1 minute.

[0135] 4) Remove the hammer and measure the height (Ha) after 1 minute of recovery.

[0136] 5) The recovery rate was calculated as a percentage using the following formula 1.

[0137] [Formula 1]

[0138] Volume recovery rate (%) = Ha / Hb x 100%

[0139]

Table 2

[0140]

[0141] From the physical property measurement results in Table 2 above, the down fillings of Examples 1 to 6 have a warmth retention of 2.00 CLO or more, an air permeability of 100 CFM or more, and a good quick-drying property of 30% or more without shedding. In addition, it can be confirmed that the down fillings of Examples 1 to 6 have an excellent recovery rate of more than 83.0%.

[0142] On the other hand, Comparative Example 1 using a small amount of HCT short fibers has a problem of slightly lower recovery rate compared to Examples 2 and 3. In addition, Comparative Example 2 using HCT short fibers in an amount exceeding 18% by weight has good physical properties such as warmth retention, quick drying, and breathability, but has a problem of a relatively rapid decrease in recovery rate compared to Examples 2 and 3.

[0143] Comparative Example 3 using a very small amount of 25% by weight of mixed down had a problem of having a warmth retention lower than 2.0 CLO, although having other good physical properties.

[0144] Compared with other embodiments and comparative examples in which hair loss did not occur, comparative example 4, which used an excessive amount of mixed down and a relatively small amount of core-sheath composite fiber, had a hair loss problem, and had problems of decreased quick-drying properties and a significantly decreased recovery rate.

[0145] The basis weight of the web layer is 65 g / m 2 Although the physical properties of Comparative Example 5 such as warmth retention, quick drying, and breathability are good, the problem is that the warmth retention is lower than 2.00CLO. The basis weight of the mesh layer is 160g / m 2 Although the warmth retention of Comparative Example 6 is good, the quick-drying property and breathability are relatively poor and the recovery rate is less than 80%.

[0146] Experimental Example 2: Measurement of Elasticity

[0147] In terms of elasticity, a high elongation value is interpreted as an excellent product, but it is necessary to consider both the elongation and recovery values ​​to confirm whether the durability and appearance are well maintained. Generally speaking, the smaller the residual elongation (or growth rate, the irrecoverable part), the greater the recovery, and the better the performance.

[0148] The elasticity was measured according to ASTM D3107. The specific measurement method is as follows. The device used in the test is shown in the figure. Figure 4 middle.

[0149] 1) Take six samples of 2.5 inches long x 22 inches wide with the length direction parallel to the stretch direction, and untie the same number of threads from both sides of the test piece to produce a width of 2.00 (± 0.05) inches.

[0150] 2) The ends of the STRETCH test piece in the length direction were folded about 1.25 inches, a 1-inch portion was sewed, and the test piece was spread out on a flat surface without external force for 30 minutes.

[0151] 3) Place the specimen under standard conditions of 21 (±1) °C and 65 (±2)% RH for 4 hours.

[0152] 4) Mark the benchmark in the center of the specimen (minimum length: 10 (±0.

[0153] 05) inches).

[0154] 5) Hang one end of the sewn annular specimen on the upper fixture, measure the length of the marked reference part of the specimen, and record it in units of 1 mm.

[0155] 6) Insert the dowel pin into the lower loop of the specimen and hang a 4lbs or 3lbs hammer.

[0156] 7) Cycle 3 times to apply a load of 0 to 4 lbs (3 lbs) to the specimen.

[0157] 8) Measure the stretch degree after 10 seconds or 30 minutes.

[0158] 9) Using the clamp of the tensiometer, stretch and fix to 85% of the length (H) of the calculated stretch percentage.

[0159] 10) After fixing in tension for 30 minutes, remove the sample from the lower fixture.

[0160] 11) Measure the benchmark value for each Client Time Option and record it in units of 1 mm.

[0161] The residual extension or growth rate is calculated according to Formula 2, the recovery rate is calculated according to Formula 3, and the stretch rate is calculated according to Formula 4.

[0162] [Formula 2]

[0163] Residual Extension = growth, %) = [{(original length + unrecovered length) - original length} / original length] X 100%

[0164] [Formula 3]

[0165] Recovery rate (%) = [{maximum extension length - (original length + unrecovered length)} / (maximum extension length - original length)] X 100%

[0166] [Formula 4]

[0167] Elongation (or elongation, %) = [{(maximum elongation length) - original length} / original length] x 100%

[0168] In Table 3 below, the longitudinal direction refers to the warp direction of the fabric constituting the sheet layer of the down filling, and the transverse direction refers to the weft direction of the fabric constituting the sheet layer of the down filling. The measured values ​​of physical properties in Table 3 represent the average of three measured values.

[0169]

Table 3

[0170]

[0171]

Table 4

[0172]

[0173] As can be seen from Tables 3 and 4 above, in Examples 1 to 6 showing the down filling of the present invention, the whole has a low residual elongation and a high recovery rate, and is a product with high elasticity.

[0174] In contrast, in Comparative Example 1 using less than 9 wt % of HCT short fibers and more than 21 wt % of RSS short fibers, there were problems in that the residual elongation was low and the recovery rate was very low.

[0175] Furthermore, compared with Example 5, Comparative Example 2 using more than 18 wt % of HCT short fibers and less than 13 wt % of RSS short fibers has a problem of having a high residual elongation and a low recovery rate.

[0176] In addition, in Comparative Example 3 using a small amount of mixed down, as previously confirmed in Experimental Example 1, its warmth retention is poor, and poor results are shown in terms of residual elongation and recovery, which may be the result of relatively excessive use of non-elastic core-skin composite fibers. In contrast, Comparative Example 4 shows excellent warmth retention compared to Example 6, but problems of high residual elongation and relatively low recovery are found.

[0177] In addition, the basis weight of the nonwoven fabric is 65g / m 2 In Comparative Example 5, the residual elongation and recovery rate are good, but as confirmed in Experimental Example 1, there is a problem of low warmth retention, and compared with Example 6, the basis weight of the nonwoven fabric is 160g / m 2 In Comparative Example 5, although the residual elongation is low, there is a problem that the restoring force is extremely low.

[0178] The above embodiments and experimental examples demonstrate that the down filling of the present invention still has excellent warmth retention within a low basis weight range and excellent four-way (or multi-directional) elasticity, so the down filling of the present invention can provide an ultra-light functional down filling product.

Claims

1. A mesh material for down filling, wherein: include: Comprising a mixed down of one or more selected from goose down and duck down; Non-stretchable low melting point sheath-core composite fiber; Hollow conjugate stretched HCT short fibers and ordinary solid siliconized fiber RSS short fibers.

2. The down filling net according to claim 1, wherein: The non-stretchable low-melting-point core-skin composite fiber has a sheath portion with a melting point of 100° C. to 150° C. and a core portion with a melting point of 250° C. or more. The HCT short fibers and the RSS short fibers have a melting point of 260° C. or higher.

3. The down filling net according to claim 1, wherein: The mixed down comprises 15 to 30% by weight of feathers and 70 to 85% by weight of down.

4. The down filling net according to claim 1, wherein: The non-stretchable low-melting-point core-skin composite fiber has an average fineness of 3.0 de to 5.0 de, an average fiber length of 45 mm to 60 mm, The HCT short fibers have an average fineness of 2.0 de to 3.5 de, an average fiber length of 45 mm to 60 mm, and a crimp number of 15 to 23 per inch. The average fineness of the RSS short fibers is 2.0 de to 3.5 de, and the average fiber length is 45 mm to 60 mm.

5. The down filling net according to claim 1, wherein: include: 25.0 wt% to 50.0 wt% of the mixed down, 9.0 wt% to 18.0 wt% of the HCT short fibers, 13.0 wt% to 21.0 wt% of the RSS short fibers and the balance of 100 wt% of the non-stretchable low-melting core-sheath composite fibers.

6. The down filling net according to any one of claims 1 to 5, wherein: The basis weight of the down filling mesh is 70g / m 2 Up to 150g / m 2 .

7. An ultralight down filler with four-way high elasticity and high warmth retention, wherein: include: A mesh layer, composed of the mesh for down filling according to claim 6; as well as a sheet layer, which is laminated on the upper and lower parts of the mesh layer and combined with the mesh layer, The sheet layer comprises a multi-directional stretch fabric with a mesh structure woven from high-elastic polyester yarn. The mesh layer and the sheet layer are a composite sheet material that is integrated without cold spots.

8. The ultra-light down filler with four-way high elasticity and high warmth retention according to claim 7, wherein: An acrylic resin layer is included between the mesh layer and the sheet layer.

9. The ultra-light down filler with four-way high elasticity and high warmth retention according to claim 7, wherein: When the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 hour, The thermal insulation capacity measured according to ASTM D1518 method meets 2.00CLO or above. The air permeability measured according to ASTM D737 method meets 100 cubic feet per minute or more.

10. The ultra-light down filler with four-way high elasticity and high warmth retention according to claim 7, wherein: When the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 hour, The drying rate after 1 hour measured according to JIS L 1096 method satisfies 30.0% or more, The recovery rate meets 83.0% or more.

11. The ultra-light down filler with four-way high elasticity and high warmth retention according to claim 7, wherein: When the basis weight of the web layer is 80 g / m 2 Up to 100g / m 2 hour, The residual elongation after 30 seconds measured according to ASTM D3107 and calculated by Formula 2 satisfies 6.5% or less in the longitudinal direction and 8.0% or less in the transverse direction, The recovery rate after 30 seconds measured according to the ASTM D3107 method and calculated by Formula 3 satisfies 70.0% or more in the longitudinal direction and 65.0% or more in the transverse direction. [Formula 2] Residual Extension = growth, %) = [{(original length + unrecovered length) - original length} / original length] X 100% [Formula 3] Recovery rate (Recovery, %) = [{maximum extension length - (original length + unrecovered length)} / (maximum extension length - original length)] X 100%.

12. A method for manufacturing an ultralight down filling with four-way high elasticity and high warmth retention, wherein: Including the execution of the following processes: Step 1, supplying the yarn in a packaged state to a supply unit; Step 2, performing bag breaking and bag opening processes on the yarn supplied to the supply unit; Step 3, combing the unpacked yarn; Step 4, processing the combed yarn into a mesh; Step 5, coating acrylic resin on both sides of the mesh, and then performing a drying process; as well as Step 6, subjecting the mesh fixed with the acrylic resin to surface heat treatment, laminating sheets on both sides of the mesh, and then rolling with a heated roller, and then packaging.

Citation Information

Patent Citations

  • Air-cured batting insulation

    CN109996913A

  • Composite down feather sheet with elastic adhesive webs

    CN110325677A

  • Composite eiderdown silk

    CN201062201Y

  • Wadding materials

    US4477515A

  • Durable pilling resistant nonwoven insulation

    WO2022177969A1